Evolution of Activists: Prison Women's Writings as Change Agent for their Communities - Irene C. Baird (Adult Education Research Conference, 2001)
Within the context of a Freirian/humanities adult education program for incarcerated women, 1972 militant women's poetry serendipitously precipitated the emergence of an activist perspective among "repeaters" for effecting change within their community, confirming theoretical constructs regarding the development of a confident, meaningful "voice" for social engagement.